Improved LayerWise Theory method application to stress analysis for composite tube in pure bending. (January 2019) - Zhang, C; Chang, R
Abstract: An improved approach using LayerWise theory (LWT) is developed for the stress analysis in pure bending composite tubes. The variables in the circumferential direction are separated from the local displacement, so the eigenvalue techniques are avoided. Then the composite tube is discretized only in the radial direction, and the related displacement in the local displacement is assumed as the simple interpolation polynomial function. Based on the principle of minimum potential energy, the local nodal variables are solved to calculate the strains and stresses for the composite tube. Several composite tubes are analyzed to illustrate the proposed approach feasibility. Besides, the exact solution by unified connected parameter method is employed for comparison. They are in good agreement with each other.